Assimilation and Cohort Effects for German Immigrants - Sebastian Gundel; Heiko Peters (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Demographic change and the rising demand for highly qualified labor in Germany attracts notice to the analysis of immigration. In addition, the pattern of immigration changed markedly during the past decades. Therefore we use the latest data of the German Socioeconomic Panel up to the year 2006 in order to investigate the economic performance of immigrants. We perform regressions of three pooled cross sections (1986, 1996, 2006) to estimate assimilation and quality of immigrants as reflected by their earnings. Further we take the heterogeneity of immigrants into account by separating them by country of origin. The rising wage inequality in Germany since the mid nineties will also be considered. We find a negative wage gap and a yearly assimilation rate of 2.3 percent. Due to a changing immigration pattern the cohort quality is declining.
Keywords: J31; J61; C21; 330; Assimilation; immigrants; cohort quality; Germany